A study of culture confirmed cases of extrapulmonary tuberculosis in a tertiary care hospital from Western Maharashtra, India - Nakate, Prasanna Chhagan; Kashetty, Virendra Ashok; Ghatole, Mangala Prakash (International Journal of Research in Medical Sciences, 2017)
Background: The proportion of cases of extrapulmonary tuberculosis (EPTB) has increased in India in recent years. Since the disease can affect virtually all organs, has an atypical clinical presentation, the clinical samples for laboratory diagnosis are sometimes difficult to procure, the confirmation of diagnosis is often delayed. With this background, the present study was undertaken to identify the culture confirmed cases of EPTB from clinically suspected cases, to identify the patient related factors associated with the disease and common sites of involvement in these patients. Methods: The study comprised of 143 patients clinically suspected to have EPTB. Relevant clinical samples were collected from these patients according to the anatomical site involved. Confirmation of diagnosis was done by mycobacterial culture using Lowenstein Jensen (L-J) medium. Results: Out of 143 specimens, 42 (29.37%) were culture positive for mycobacteria (culture confirmed cases). Higher proportion of EPTB was found in females (36.92%) than males (23.08%). Maximum patients of EPTB belonged to the age group of 21-40 years (22 cases out of 57, 38.60%). Out of the 17 HIV positive patients, 6 (35.29%) were culture positive for mycobacteria. Maximum culture positivity was found with pus samples from bone and joint (44.12%) followed by lymph nodes (42.42%). Conclusion: It was found that female sex, younger age (below 40 years) and HIV infection were found to be commonly associated with extrapulmonary tuberculosis. While many studies report TB lymphadenitis as the most common form of EPTB, in our study bone and joint was found to be the commonest site involved in the disease followed by lymph node. Since EPTB has become more common than previously and is difficult to diagnose, it is important to have greater clinical suspicion for the disease and to take appropriate laboratory help for its confirmation.